Monoolein Assisted Oil-Based Transdermal Delivery of Powder Vaccine - Momoko Kitaoka; Atsushi Oka; Masahiro Goto (MDPI AG, 2020)
An increasing number of protein vaccines have been researched for cancer, inflammation, and allergy therapies. Most of the protein therapeutics are administered through injection because orally-administered proteins are metabolized by the digestive system. Although transdermal administration has received increasing attention, the natural barrier formed by the skin is an obstacle. Monoolein is a common skin penetration enhancer that facilitates topical and transdermal drug delivery. Conventionally, it has been used in an aqueous vehicle, often with polyhydric alcohols. In the current study, monoolein was dissolved in an oil vehicle, isopropyl myristate, to facilitate the skin permeation of powder proteins. The skin permeabilities of the proteins were examined in-vivo and ex-vivo. Monoolein concentration-dependently enhanced the skin permeation of proteins. The protein permeability correlated with the zeta potential of the macromolecules. Dehydration of the stratum corneum (SC), lipid extraction from the SC, and disordering of ceramides caused by monoolein were demonstrated through Fourier transform infrared spectroscopic analysis and small-angle X-ray scattering analysis. An antigen model protein, ovalbumin from egg white, was delivered to immune cells in living mice, and induced antigen-specific IgG antibodies. The patch system showed the potential for transdermal vaccine delivery.